Education of National Values and Local Wisdom in Junior High Schools - Teuku Alfiady; Siraj; Fajriana (LPPM Universitas Malikussaleh, 2024)
The aim of this research is focused on efforts to produce an overview of the potential and implementation of national values and local wisdom that will be integrated into the learning process. The initial field analysis reveals a gap between expectations and reality regarding the implementation of Aceh Qanun Number 11 of 2014, resulting in the integrated education system in Lhokseumawe City not being fully realized. The type of research used is descriptive qualitative research. This research was conducted at Junior High School in Lhokseumawe. The subjects of this study were teachers, students, and parents, while the object of the research was the implementation of national values and local wisdom to be integrated into the learning process. The data analysis technique used is the interactive: data reduction, data presentation, and conclusion drawing. The research findings indicate that the integration of national values and local wisdom in teaching leads to the development of students' character through habituation patterns and the creation of a conducive school environment. This process shapes students' attitudes and behaviors, resulting in students who possess academic abilities, skills, and noble character, all of which are beneficial to religion, the nation, and the state.